Applying host disease status biomarkers to therapeutic response monitoring in invasive aspergillosis patients. (22nd January 2018) - Zhao, Yanan; Nagasaki, Yoji; Paderu, Padmaja; Sugrue, Michele W; Leather, Helen L; Wingard, John R; Perlin, David S
Abstract: One critical factor impeding successful management of invasive aspergillosis (IA) is the lack of reliable biomarkers to assess therapeutic response. We hypothesized that changes in certain host biomarkers reflect the nature of infection status and disease progression. Upon primary IA diagnosis, these disease status biomarkers can be monitored to track response to antifungal therapy and provide early markers that prognosticate likelihood of response. Herein, we analyzed serum levels of three prominent host disease status biomarkers C-reactive protein (CRP), haptoglobin (Hp), and annexin A1 (ANXA1) in IA patients during antifungal therapy. A total of 81 serial serum samples were collected at five or six different time points relative to IA diagnosis from 15 probable IA patients (10 acute leukemia [AL] and five hematopoietic stem cell transplantation [HSCT]). Of note, different biomarker profiles were observed in AL and HSCT patients, as not only levels of markers were significantly lower in HSCT patients but also more prominent interconnections among markers were observed in AL patients. Using a composite evaluation, patients were categorized as responders, nonresponders, and stable cases at last specimen. For AL responders, typical biomarker profiles were high initially but rapidly decreased for CRP and Hp post antifungal therapy, while low initial ANXA1 values were restored to normal levels after treatment. In contrast, CRP and Hp were persistently elevated whilst ANXA1 remained low throughout therapy in AL non-responders. As a pilot proof-of-concept study, our work demonstrates the great potential of using host biomarkers to monitor early therapeutic response in leukemia patients.